Efektivitas Layanan Bimbingan Klasikal Model Teams Games Tournaments untuk Mereduksi Burnout Akademik - Ilmawan, Ananda Ikhsan; Santosa, Hardi (JURKAM: Jurnal Konseling Andi Matappa, 2024)
The aim of this research is to determine the effectiveness of classical guidance services using the teams games tournaments model in reducing academic burnout. This research is a quantitative research that uses a pre-experimental study with a one group pre-test post-test research design. The population in this study involved all class XII majoring in automotive light vehicle engineering (TKRO). The sample in this study was class XII TKRO 2, totaling 25 students who were taken using purposive sampling technique. Data collection techniques and instruments used structured interviews and an academic burnout scale. The data analysis technique in this research is the Wilcoxon Signed Rank Test statistical test. The results of this research show that there are differences in the average academic burnout scores among students. The average score before the treatment was given was 141. Meanwhile the average score after the treatment was given decreased by 26 points to 115. The results of the statistical data analysis of the Wilcoxon Signed Rank Test show the Asymp value. Sig (2-tailed) is 0.000 (<0.05) so Ho is rejected and Ha is accepted. Therefore, it can be concluded that the classical guidance service model of teams games tournaments is effective in reducing academic burnout.